2021
DOI: 10.21930/rcta.vol22_num2_art:1699
|View full text |Cite
|
Sign up to set email alerts
|

Análisis y reducción de costos alimenticios asociados a la producción láctea de un sistema bovino semiespecializado, mediante el uso de la metodología AHP

Abstract: La producción de leche es un renglón importante dentro del sector agropecuario y la economía de un país. En México, el aporte del sector agropecuario al producto interno bruto (PIB) nominal es del 4,2 %, con una participación del 30,2 % de la ganadería. Este tipo de producción presenta diversos sistemas mejorados para aumentar la tasa de rendimiento. Sin embargo, es necesario conocer los costos de producción asociados a la alimentación de los bovinos en términos de materia seca consumida. En esta investigación… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…HC had within its sub-criteria, F (weight = 0.0916), Fe (weight = 0.0714), M (weight = 0.3778), and E (weight = 0.0305), that were prioritized according to the main study objective using AHP and TCA. The findings are consistent with that of other researchers [84][85][86]88,89] who reported that farmers were constrained by feed and fertilizer unaffordability which resulted in low milk productivity and low net profits. However, for those farmers who can afford high quality feed, great net returns were observed, and their milk production quotas were high [86].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…HC had within its sub-criteria, F (weight = 0.0916), Fe (weight = 0.0714), M (weight = 0.3778), and E (weight = 0.0305), that were prioritized according to the main study objective using AHP and TCA. The findings are consistent with that of other researchers [84][85][86]88,89] who reported that farmers were constrained by feed and fertilizer unaffordability which resulted in low milk productivity and low net profits. However, for those farmers who can afford high quality feed, great net returns were observed, and their milk production quotas were high [86].…”
Section: Discussionsupporting
confidence: 92%
“…The findings are consistent with that of other researchers [84][85][86]88,89] who reported that farmers were constrained by feed and fertilizer unaffordability which resulted in low milk productivity and low net profits. However, for those farmers who can afford high quality feed, great net returns were observed, and their milk production quotas were high [86]. High costs of electricity were also reported in literature, where farmers spent around 5000 euros on electricity for production yearly [90][91][92] and proposed as an alternative the use of solar power to alleviate the high electricity bills and production glitches [67].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Appropriately, the production cost is a limiting factor for the increase in the income of the producers, the production of cattle demands large expenses with food, reaching 80% (GREENWOOD, 2021). To avoid this situation, techniques, such as handling the disposal of the animal in the field, the application of plant by-products with a high protein and/or mineral concentration, and the use of forage crops adapted to the region and which have lower production costs than those normally explored by the producer must be adopted (CREMILLEUX et al, 2022;PATERNINA-ACOSTA et al, 2021;CAPPELLOZZA et al, 2021).…”
mentioning
confidence: 99%